Incentives and Performance Governance of Research Organizations - Welpe, Isabell M.; Welpe, Isabell M.; Wollersheim, Jutta.; Wollersheim, Jutta.; Ringelhan, Stefanie.; Ringelhan, Stefanie.; Osterloh, Margit.; Osterloh, Margit. (Springer International Publishing : Imprint: Springer, 2015)
This book contributes to the current discussion in society, politics and higher education on innovation capacity and the financial and non-financial incentives for researchers. The expert contributions in the book deal with implementation of incentive systems at higher education institutions in order to foster innovation. On the other hand, the book also discusses the extent to which governance structures from economy can be transferred to universities and how scientific performance can be measured and evaluated. This book is essential for decision-makers in knowledge-intensive organizations and higher-educational institutions dealing with the topic of performance management.